2021
DOI: 10.3390/nu14010004
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Therapies and Their Influence on the Intestinal Microbiome in Pediatric Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a chronic, autoimmune disorder of the gastrointestinal tract with numerous genetic and environmental risk factors. Patients with Crohn’s disease (CD) or ulcerative colitis (UC) often demonstrate marked disruptions of their gut microbiome. The intestinal microbiota is strongly influenced by diet. The association between the increasing incidence of IBD worldwide and increased consumption of a westernized diet suggests host nutrition may influence the progression or treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 122 publications
0
16
0
1
Order By: Relevance
“…Dietary interventions have been extensively explored for the treatment of IBD, with a large variety diets being investigated for uses in either Crohn's disease (CD) or ulcerative colitis (UC). 47 These diets include, exclusive enteral nutrition (EEN), 48,49 Crohn's disease exclusion diet (CDED), [50][51][52] specific carbohydrate diet, 53 LFD, 54 Mediterranean diet (MD), 55 Crohn's Disease TReatment with EATing diet (CD-TREAT) 56 and partial enteral nutrition. 47 Only two of these diets have proven clinical efficacy in CD treatment and evidence to show their impact on the GI microbiome, EEN 48,49,57 and CDED.…”
Section: Dietary Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary interventions have been extensively explored for the treatment of IBD, with a large variety diets being investigated for uses in either Crohn's disease (CD) or ulcerative colitis (UC). 47 These diets include, exclusive enteral nutrition (EEN), 48,49 Crohn's disease exclusion diet (CDED), [50][51][52] specific carbohydrate diet, 53 LFD, 54 Mediterranean diet (MD), 55 Crohn's Disease TReatment with EATing diet (CD-TREAT) 56 and partial enteral nutrition. 47 Only two of these diets have proven clinical efficacy in CD treatment and evidence to show their impact on the GI microbiome, EEN 48,49,57 and CDED.…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…47 These diets include, exclusive enteral nutrition (EEN), 48,49 Crohn's disease exclusion diet (CDED), [50][51][52] specific carbohydrate diet, 53 LFD, 54 Mediterranean diet (MD), 55 Crohn's Disease TReatment with EATing diet (CD-TREAT) 56 and partial enteral nutrition. 47 Only two of these diets have proven clinical efficacy in CD treatment and evidence to show their impact on the GI microbiome, EEN 48,49,57 and CDED. [50][51][52] Exclusive enteral nutrition involves the replace of all food and beverages with a liquid meal replacement, which can induce remission in 80%-85% of patients with CD.…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…Interests in the diet’s ability to alter the gut microbiome as a therapeutic strategy among patients with IBD has grown tremendously in recent years ( Figure 2 ) [ 63 ]. Several nutritional therapies have been explored among pediatric patients with IBD.…”
Section: Dietary Modulation Of the Gut Microbiome In Ibdmentioning
confidence: 99%
“…For example, the Crohn’s Disease Exclusion Diet (CDED) is a high protein, low-fat diet that includes foods such as chicken, fish, eggs, rice, potatoes, and various fruits and vegetables. This intervention has been effective for mild to moderate CD in children, as well as for patients whose response to anti-TNF biologic treatments plateaued [ 63 ]. Levine et al found that remission in the CDED groups was associated with changes in microbial diversity, a decrease in Proteobacteria and an increase in Firmicutes , particularly Clostridiales .…”
Section: Dietary Modulation Of the Gut Microbiome In Ibdmentioning
confidence: 99%
“… 5 , 6 Although nutritional management, 5‐aminosalicylic acid (5‐ASA), glucocorticoids, immunosuppressive agents, and biologics may be useful in the treatment of IBD in children, there still lacks biomarkers to reflect the risk and characteristics of IBD in children, which could hinder the in‐time management of IBD in children. 4 , 7 , 8 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%